2013
DOI: 10.1371/journal.pone.0084141
|View full text |Cite
|
Sign up to set email alerts
|

Hydrokinetic Turbine Effects on Fish Swimming Behaviour

Abstract: Hydrokinetic turbines, targeting the kinetic energy of fast-flowing currents, are under development with some turbines already deployed at ocean sites around the world. It remains virtually unknown as to how these technologies affect fish, and rotor collisions have been postulated as a major concern. In this study the effects of a vertical axis hydrokinetic rotor with rotational speeds up to 70 rpm were tested on the swimming patterns of naturally occurring fish in a subtropical tidal channel. Fish movements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 50 publications
2
69
0
1
Order By: Relevance
“…Two GoPro R HERO2 cameras mounted on a calibrated frame with 60 cm base separation were used for data collection. Specific calibration (Hammar et al, 2013) and additional methodological details can be found in previous investigations. Once positioned, the cameras were left to record for 50 min of continuous filming, with an additional 5 min at the start of all videos to exclude disturbance effects.…”
Section: Camera Surveys and Assessment Of Fish Assemblagesmentioning
confidence: 99%
“…Two GoPro R HERO2 cameras mounted on a calibrated frame with 60 cm base separation were used for data collection. Specific calibration (Hammar et al, 2013) and additional methodological details can be found in previous investigations. Once positioned, the cameras were left to record for 50 min of continuous filming, with an additional 5 min at the start of all videos to exclude disturbance effects.…”
Section: Camera Surveys and Assessment Of Fish Assemblagesmentioning
confidence: 99%
“…For example, video monitoring has indicated that benthic reef fish were able to avoid a vertical-axis, cross-flow HK turbine even when in close proximity to it (Hammar et al 2013). In fact, no turbine blade collisions were observed by Hammar et al (2013).…”
Section: Comparison Of Hk Turbine Typesmentioning
confidence: 99%
“…It was seen that the new turbine operates in average 1117h and generates 420 kWh in a year whereas the rotating turbine just operates 41h and generates 80kWh. Due to their small size hydrokinetic turbines do not harm fish, which is a large advantage compared to the run-off river barrage power plants [3,10].…”
Section: Resultsmentioning
confidence: 99%
“…Turbines with a variable immersion depth increase the number of exploitable spots within a river, due to the adaptability on lower water levels. Furthermore, experiments have shown that single hydrokinetic turbines do not harm fish, due to their slow motion and a construction which makes it for the fish possible to easily pass by [3].…”
Section: Introductionmentioning
confidence: 99%